The HepTestContest: a global innovation contest to identify approaches to hepatitis B and C testing - Joseph D. Tucker; Kathrine Meyers; John Best; Karyn Kaplan; Razia Pendse; Kevin A. Fenton; Isabelle Andrieux-Meyer; Carmen Figueroa; Pedro Goicochea; Charles Gore; Azumi Ishizaki; Giten Khwairakpam; et al. (BMC Infectious Diseases, 2017)
Abstract Background Innovation contests are a novel approach to elicit good ideas and innovative practices in various areas of public health. There remains limited published literature on approaches to deliver hepatitis testing. The purpose of this innovation contest was to identify examples of different hepatitis B and C approaches to support countries in their scale-up of hepatitis testing and to supplement development of formal recommendations on service delivery in the 2017 World Health Organization hepatitis B and C testing guidelines. Methods This contest involved four steps: 1) establishment of a multisectoral steering committee to coordinate a call for contest entries; 2) dissemination of the call for entries through diverse media (Facebook, Twitter, YouTube, email listservs, academic journals); 3) independent ranking of submissions by a panel of judges according to pre-specified criteria (clarity of testing model, innovation, effectiveness, next steps) using a 1-10 scale; 4) recognition of highly ranked entries through presentation at international conferences, commendation certificate, and inclusion as a case study in the WHO 2017 testing guidelines. Results The innovation contest received 64 entries from 27 countries and took a total of 4 months to complete. Sixteen entries were directly included in the WHO testing guidelines. The entries covered testing in different populations, including primary care patients (n = 5), people who inject drugs (PWID) (n = 4), pregnant women (n = 4), general populations (n = 4), high-risk groups (n = 3), relatives of people living with hepatitis B and C (n = 2), migrants (n = 2), incarcerated individuals (n = 2), workers (n = 2), and emergency department patients (n = 2). A variety of different testing delivery approaches were employed, including integrated HIV-hepatitis testing (n = 12); integrated testing with harm reduction and addiction services (n = 9); use of electronic medical records to support targeted testing (n = 8); decentralization (n = 8); and task shifting (n = 7). Conclusion The global innovation contest identified a range of local hepatitis testing approaches that can be used to inform the development of testing strategies in different settings and populations. Further implementation and evaluation of different testing approaches is needed.